2017
DOI: 10.1093/dote/dox041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tissue chromogranin A (CgA) immunostaining and clinicohistopathological changes for the 125 Chinese patients with primary small cell carcinoma of the esophagus

Abstract: The rarity of primary small cell carcinoma of the esophagus (PSCE) has limited the clinical feature and survival analysis with large sample size. Tissue chromogranin A (CgA) protein expression has been reported to be a useful biomarker for diagnosing PSCE. Interestingly, recent studies have indicated tissue CgA as a significant prognostic marker in multiple human cancers, but without PSCE. The present study, thus, was undertaken to characterize the clinicopathological changes and to evaluate the associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Surgical treatment of malignant diseases can be either simultaneously performed with CABG or via a staged approach a few weeks later. However, whether to select either one-stage or two-stage operation remains controversial [ 12 , 13 ]. A two-stage procedure is two surgical traumas, which may delay the tumor resection and doubles postoperative pains and treatment costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical treatment of malignant diseases can be either simultaneously performed with CABG or via a staged approach a few weeks later. However, whether to select either one-stage or two-stage operation remains controversial [ 12 , 13 ]. A two-stage procedure is two surgical traumas, which may delay the tumor resection and doubles postoperative pains and treatment costs.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous procedure has gradually been adopted to perform various cardiac and noncardiac operations, including pulmonary lobectomy, esophagectomy, gastrectomy, and colectomy [ 14 , 15 ]. This approach has been mainly performed in thoracic carcinoma patients and may solve two problems through a single incision [ 12 , 15 ]. However, in China which has a large population, there are few reports of combined esophagectomy and off-pump CABG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results failed to testify the prognostic value of Ki67, but showed that negative TTF-1, NSE, Syn or CgA staining was related with a poor survival. In a study enrolled 125 Chinese patients with ESCC showed patients with higher CgA protein expression had a superior long survival than those without CgA expression (P=0.037) (33). Studies about other types of tumor concluded that the percentage of tumor cells with the ability to produce neuroendocrine markers was a significant independent prognostic factor associated with favorable outcomes (24,34,35).…”
Section: A B C D E Fmentioning
confidence: 99%
“…[ 1 ] SCC may also be found in digestive tract, cervix, ovary, bladder, prostate, and endometrium. [ 2 5 ] Although SCC can be found in different anatomic sites, similarities, such as histological appearance, immunohistochemical expression of epithelial and neuroendocrine markers, common involvement of lymph nodes and vessels invasion, hematogenous metastasis, and unfavorable prognosis, can be observed. [ 3 ] However, the risk factors are usually different.…”
Section: Introductionmentioning
confidence: 99%